INSTRUCTIONAL COMMUNICATIONS AT EARLY CHILDHOOD EDUCATION (PAUD) AT-TAQWA KARAWANG Descriptive Qualitative Studies about Communications Instructional in Teaching and Learning Process at PAUD At-Taqwa Karawang - Hariyanto, Fajar (Jurnal Politikom Indonesiana, 2018)
ABSTRACT The ability and credibility of teachers in educating students in the school environment, can be achieved by providing useful and meaningful lessons. Student learning outcomes in the end is shown by the change of behavior so that it can be said that the learners’ learning outcomes have been reached optimally.Based on the above exposure, then the purpose of research that researchers do is the researchers want to study more deeply about instructional communication in teaching and learning process so that the achievement of learning outcomes in early childhood in At-Taqwa Karawang.Based on backgroundabove. In this study researchers used qualitative methods with qualitative descriptive approach. While the approach on descriptive research is intended for the exploration of a content specification and instructional objectives, assess entering behavior in teaching and learning process, determination instructional strategies, and organize instructional units at PAUD At-Taqwa Karawang. Referring to the results of the research, the researchers draw the following conclusions; The instructional content specification and instructional objectives are the preparatory stage wherePAUD At-Taqwa Karawang teacher prepares both in writing and orally; Assessment of entering behavioris the stage where the teacher makes a preliminary estimate of the learner by understanding the target situation and condition, psychological, and initial ability that the learner has; Determination of Instructional Strategiesused by At-Taqwa PAUD to convey information to learners. There are two strategies that used expository strategy and inquiry strategy; Organization of Instructional Unitsis the phase where the teacher convey material in the form of knowledge to learners that refers to the theme along with subtema learning. Keyword: Instructional communication, PAUD, Karawang